Spinel oxygen carrier with capability of deeply releasing lattice oxygen as well as preparation method and application of spinel oxygen carrier

By doping Cu, Mn, Ni, Ca, and Sr elements into Fe2O3 oxygen carrier, a spinel oxygen carrier with deep release lattice oxygen capacity was prepared, which solved the problems of insufficient activity, serious surface carbon in the hydrogen production of chemical chains, and achieved efficient recycling of waste plastics and efficient preparation of high-purity hydrogen.

CN119660813APending Publication Date: 2025-03-21NANJING UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411955029.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, Fe2O3 oxygen carriers have problems such as insufficient activity, serious surface carbon and poor circulation stability in the hydrogen production of chemical chains, and lack applications for waste plastics.

Method used

By doping elements such as Cu, Mn, Ni, Ca, Sr, etc. into the metal iron-based oxygen carrier AFe2O4 with spinel-type structure, the multi-metal elements are used to show a dilution effect on the A-position atoms of the spinel-type oxygen carrier, and combined with the polymetal effect that promotes lattice oxygen release, a spinel oxygen carrier with deep release lattice oxygen capacity is prepared.

Benefits of technology

It has achieved efficient recycling and utilization of waste plastics and efficient preparation of high-purity hydrogen, overcomes the problems of insufficient activity of Fe2O3 oxygen carrier, serious carbon surface area and poor circulation stability, improves carbon conversion and hydrogen yield, and meets the requirements of industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660813A_ABST
    Figure CN119660813A_ABST
Patent Text Reader

Abstract

The invention discloses a spinel oxygen carrier with the capability of deeply releasing lattice oxygen as well as a preparation method and application thereof, and belongs to the related technical field of hydrogen energy preparation. Elements such as Cu, Mn, Ni, Ca, Sr and the like are doped into a metal iron-based oxygen carrier AFe2O4 with a spinel type structure according to an equal molar ratio, a dilution effect is shown on A-site atoms of the spinel type oxygen carrier AFe2O4 by virtue of multiple metal elements, and a multi-metal effect for promoting lattice oxygen release is combined. In addition, the spinel type oxygen carrier (AFe2O4) has excellent adsorption capacity and cycling stability, and the novel oxygen carrier is applied to chemical looping hydrogen production (CLR) to realize recycling of waste plastics and efficient preparation of high-purity hydrogen. Therefore, the problems of insufficient activity, serious surface carbon deposition, poor cycling stability and the like of a pure Fe2O3 oxygen carrier in chemical looping hydrogen production (CLR) are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field related to hydrogen energy preparation, and specifically relates to a spinel oxygen carrier with deep lattice oxygen release capability and a preparation method and application thereof. Background Art

[0002] Plastic pollution is serious around the world, with hundreds of millions of tons of plastic waste generated every year, most of which is difficult to degrade, posing a long-term threat to the environment. Plastic treatment methods include physical recycling, thermochemical treatment, and chemical chain hydrogen production technology. China's plastic recycling rate needs to be improved. Currently, physical recycling and incineration are the main methods, but there are efficiency and pollution problems. The waste plastic recycling industry faces challenges such as dominance by small and medium-sized enterprises and insufficient technological innovation. In the future, the plastic circular economy and chemical chain hydrogen production technology are expected to achieve sustainable development, increase recycling rates, and reduce environmental pollution.

[0003] With the challenge of global climate change, hydrogen energy, as a clean energy, is regarded as an important carrier for achieving low-carbon energy transformation. At present, due to the high cost of green hydrogen production, the economic feasibility of green hydrogen faces challenges. However, under the multiple effects of technological progress, the decline in the cost of renewable energy power generation, policy guidance and corporate social responsibility awareness, the production cost of green hydrogen is expected to continue to decline, which will make the economic advantages of green hydrogen more prominent.

[0004] Chemical chaining technology is a process that completes a specific chemical reaction step by step through a chemical medium. It has important applications in energy conversion and carbon dioxide capture. This technology achieves oxygen transfer and fuel combustion by circulating a solid oxygen carrier between two reactors, thereby avoiding direct contact with air and achieving efficient CO2 capture.

[0005] Chemical looping hydrogen production technology is an important application direction of chemical looping technology. It produces hydrogen through processes such as chemical looping steam reforming or autothermal chemical looping reforming, while capturing CO2, and has the potential to improve energy conversion efficiency and reduce environmental pollution. Compared with chemical looping reforming technology (CLR), chemical looping hydrogen production technology (CLH) has the advantages of not requiring external CO2 and H2 separation equipment and low energy consumption. In addition, this process only requires one oxygen carrier (OC) to simultaneously capture high-concentration CO2 and prepare high-purity H2.

[0006] However, unlike other chemical looping processes, chemical looping hydrogen production technology requires not only that the oxygen carrier has traditional properties, but also that the oxygen carrier must have the ability to react with water vapor to generate hydrogen. At present, many researchers have shown that Fe2O3 is the most suitable oxygen carrier in chemical looping hydrogen production technology (CLH), but pure Fe2O3 oxygen carriers have problems such as insufficient activity, severe surface carbon accumulation and poor cycle stability, which significantly affect the H2 production and purity. In addition, the existing technology also lacks the application of waste plastics in chemical looping hydrogen production (CLR).

[0007] Based on the above reasons, this application is filed. Summary of the invention

[0008] Based on the above reasons, in view of the problems or defects in the prior art, the purpose of the present invention is to provide a spinel oxygen carrier with deep lattice oxygen release ability and its preparation method and application, so as to solve or at least partially solve the above technical defects in the prior art: the present invention dopes Cu, Mn, Ni, Ca, Sr and other elements in equal molar ratios into the metal iron-based oxygen carrier AFe2O4 of the spinel structure, and uses the multi-metal elements to show a dilution effect on the A-site atom of the spinel oxygen carrier (AFe2O4), combined with the multi-metal effect that promotes the release of lattice oxygen. In addition, the spinel oxygen carrier (AFe2O4) has excellent adsorption capacity and cyclic stability, and the new oxygen carrier is applied to chemical chain hydrogen production (CLR) to achieve the recycling of waste plastics and the efficient production of high-purity hydrogen. In this way, the problems of insufficient activity, serious surface carbon accumulation and poor cyclic stability of pure Fe2O3 oxygen carrier in chemical chain hydrogen production (CLR) are solved.

[0009] To achieve the above object, according to one aspect of the present invention, a method for preparing a spinel oxygen carrier with deep lattice oxygen release capability is provided, and the method steps are as follows:

[0010] Metal oxide, ferric oxide (Fe2O3) powder and organic solvent are mixed in order according to the proportion, and the obtained mixture is ground and then dried; then the dried precursor is calcined at a temperature of 900°C for 10 hours, and the obtained product is ground to obtain the spinel oxygen carrier with deep lattice oxygen release ability.

[0011] Furthermore, in the above technical solution, the metal oxide is at least one of CuO, MnO, NiO, CaO, and SrO.

[0012] Furthermore, in a preferred embodiment of the present invention, the metal oxide consists of copper oxide (CuO), manganese oxide (MnO), nickel oxide (NiO), calcium oxide (CaO) and strontium oxide (SrO).

[0013] Further, in the above technical solution, the metal oxide (M i )Amount of substance Mol Mi The amount of ferric oxide Mol Fe Satisfies the following relationship: (∑Mol Mi :Mol Fe )=1:1.

[0014] Furthermore, in a preferred embodiment of the present invention, when the metal oxide is composed of copper oxide (CuO), manganese oxide (MnO), nickel oxide (NiO), calcium oxide (CaO) and strontium oxide (SrO), the molar ratio of copper oxide, manganese oxide, nickel oxide, calcium oxide and strontium oxide is 1:1:1:1:1.

[0015] Furthermore, in the above technical solution, the organic solvent is any one of aromatic solvents, alcohol solvents, alkane solvents, ether solvents, nitrile solvents, and ketone solvents, or a mixture of more thereof; the amount of the organic solvent used may not be specifically limited, as long as uniform mixing of the metal oxide and ferric oxide can be achieved.

[0016] Furthermore, in a preferred embodiment of the present invention, the organic solvent is any one of anhydrous ethanol, isopropanol or polyethylene glycol.

[0017] Further, in the above technical solution, the grinding is carried out in a ball mill. Preferably, the grinding is specifically carried out at a speed of 600 rpm, with forward rotation for 30 minutes, stop rotation for 5 minutes, and reverse rotation for 30 minutes, for 5 cycles, i.e., a total rotation of 5 hours.

[0018] Furthermore, in the above technical solution, the specific drying process is as follows: put into a drying oven and dry at 120° C. for 8 hours.

[0019] According to another aspect of the present invention, a spinel oxygen carrier with deep lattice oxygen release capability is provided, which is prepared according to the above-mentioned preparation method.

[0020] According to another aspect of the present invention, there is provided an application of a spinel oxygen carrier with deep lattice oxygen release capability, wherein the application is based on chemical chaining hydrogen production technology (CLR) and uses waste plastics as raw materials to produce high-purity hydrogen, wherein the high-purity hydrogen refers to hydrogen with a purity of more than 90%.

[0021] Furthermore, in the above technical solution, the specific method of application includes the following steps:

[0022] (1) Preset the feed rate, then weigh the polypropylene (PP) powder and place it in the feeder; place the spinel oxygen carrier with deep lattice oxygen release capacity on the porous distribution plate of the quartz tube reactor according to the ratio, connect the pipeline, and check the air tightness of the device; control the flow meter to pass nitrogen to purge the entire reaction device to ensure that the tube is in an inert atmosphere;

[0023] (2) turning on the power of the fixed bed reactor to heat the vertical tube furnace and introducing a carrier gas atmosphere; after the temperature of the vertical tube furnace reaches 900° C. and remains stable, closing the oxygen intake, maintaining the flow rate of the carrier gas atmosphere unchanged, and purging the reaction device to remove residual oxygen; then turning on the power of the vibrating feeder to start feeding, and the polypropylene powder is brought into the fixed bed reactor through the feed pipe to react with the deep lattice oxygen release capacity spinel oxygen carrier until the flue gas analyzer can no longer detect the generation of gas;

[0024] (3) When the contents of all gases except nitrogen are reduced to 0, deionized water is loaded into the fixed bed reactor by a metering pump to react with the reduced oxygen carrier to produce hydrogen; when the flue gas analyzer no longer detects gas generation, the reaction is completed, the metering pump is turned off, and the experiment is ended; the hydrogen purity is the hydrogen concentration in the produced gas.

[0025] Furthermore, in the above technical scheme, the dosage relationship between the polypropylene and the spinel oxygen carrier with deep lattice oxygen release capacity in step (1) is defined as determined by the oxygen supply coefficient, wherein the oxygen supply coefficient is: oxygen supply coefficient = lattice oxygen provided by the oxygen carrier / lattice oxygen required for complete oxidation of the fuel.

[0026] Furthermore, in the above technical solution, the purity of the nitrogen in step (1) is 99.9%, and the flow rate is 200 mL / min.

[0027] Furthermore, in the above technical solution, the mass of the spinel oxygen carrier with deep lattice oxygen release capacity in step (1) is the mass of the oxygen carrier when the oxygen supply coefficient is Φ=1 and Φ=0.5 respectively.

[0028] Furthermore, in the above technical solution, the heating rate in step (2) is 5-15°C / min.

[0029] Furthermore, in the above technical solution, the carrier gas atmosphere in step (2) is composed of nitrogen and oxygen. The flow rate of the nitrogen is 150-160 mL / min, and the flow rate of the oxygen is 40-50 mL / min; the total flow rate of the carrier gas atmosphere 1 is 200 mL / min.

[0030] Preferably, step (2) is carried out in a fuel reactor (FR), step (3) is carried out in a steam reactor (SR), and the fixed bed reactor is composed of a vertical tube furnace and a quartz tube reactor.

[0031] Preferably, in the step (2), the top of the feeder is connected to inert nitrogen, and the polypropylene (PP) powder is brought into the fixed bed reactor by the nitrogen flow through the feed pipe.

[0032] Furthermore, in the above technical solution, the flow rate of the deionized water in step (3) is 0.05-0.2 mL / min.

[0033] The main raw materials used in the present invention play the following roles in the present invention:

[0034] 1.Fe occupies the B position in the deeply oxygen-releasing spinel. In the chemical chain process, Fe-based oxides can be reduced while oxidizing waste plastics to generate synthesis gas in the fuel reactor stage. Then the reduced iron-based oxides have the ability to decompose water to produce hydrogen.

[0035] 2. Equal proportions of copper, manganese, nickel, calcium and strontium jointly occupy the A position of spinel, increasing the configurational entropy, helping the oxygen carrier to maintain the spinel structure, improving its stability during the reaction process, and at the same time causing the spinel lattice distortion and promoting the deep release of lattice oxygen.

[0036] The reaction mechanism involved in the present invention is as follows:

[0037] In the fuel reactor:

[0038] (Cu 0.2 Mn 0.2 Ni 0.2 Ca 0.2 Sr 0.2 )Fe2O4+C x H y Oz (xyz depends on the type of feedstock) → CO + CO2 + H2 + CH4 + H2O + Fe 0 +Cu 0 +Mn+Ni+CaO+SrO...

[0039] In a steam reactor:

[0040] Fe 0 +Cu 0 + Mn + Ni + CaO + SrO + H2O → (Cu 0.2 Mn 0.2 Ni 0.2 Ca 0.2 Sr 0.2 )Fe2O4+H2

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] (1) The spinel oxygen carrier with deep lattice oxygen release prepared by the present invention has the advantages of high activity, high lattice oxygen content, strong selectivity of target products, outstanding hydrogen production capacity, etc., realizing the combination of waste plastic recycling and chemical chain hydrogen production, and synchronously producing synthesis gas and hydrogen. By adjusting the process parameters, waste plastic can be converted into synthesis gas, and the carbon conversion rate can reach 85.68%; the hydrogen yield in the steam reactor can reach 6.76mmol / g, and the purity can reach 93.03%, meeting the requirements of industrial application.

[0043] (2) The spinel oxygen carrier with deep lattice oxygen release capability of the present invention has a dilution effect on the A-site atom of the spinel oxygen carrier (AFe2O4) due to the doped multi-metal elements. Combined with the multi-metal effect that promotes the release of lattice oxygen, it is beneficial to improve the carbon conversion rate and hydrogen yield. At the same time, thanks to the regulation of the lattice oxygen activity of the five-element spinel oxygen carrier, waste plastics have a higher selectivity for the reaction to generate CO and H2

[0044] (3) The deep lattice oxygen release spinel oxygen carrier of the present invention, thanks to the structural characteristics of the spinel oxygen carrier, has superior cycle performance compared to Fe2O3, and overcomes other problems such as the traditional iron-based oxygen carrier Fe2O3 easily generating Fe3O4 in the steam reactor, resulting in oxygen carrier deactivation. Considering that the present invention has shown excellent results in both hydrogen production performance and cycle performance. Therefore, the five-element iron-based spinel oxygen carrier will have a good development prospect in the field of chemical chain hydrogen production (CLH), and is expected to stand out from the chemical chain technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0046] Figure 1 It is a schematic diagram of converting waste plastics into synthesis gas and hydrogen using the spinel oxygen carrier with deep lattice oxygen release capacity of the present invention.

[0047] Figure 2 This is a SEM test image of the oxygen carrier prepared in Example 6.

[0048] Figure 3 It is the XRD test pattern of the oxygen carrier prepared in Example 1-5.

[0049] Figure 4 This is the XRD test pattern of the oxygen carrier prepared in Example 6.

[0050] Figure 5It is an XPS test graph of the oxygen carrier prepared in Examples 1-6 and the oxygen carrier prepared in Comparative Example 1.

[0051] Figure 6 It is the H2-TPR test graph of the oxygen carrier prepared in Examples 1-6 and the oxygen carrier prepared in Comparative Example 1. DETAILED DESCRIPTION

[0052] The spinel-type iron-based oxygen carrier AFe2O4 (A = Cu, Ni, Ca, Sr, Mn) was studied as a new type of oxygen carrier. The results showed that the oxygen carrier has higher reactivity and cycle performance than single metal oxides. The spinel iron-based oxygen carrier has great advantages in oxygen carrying capacity, reaction rate, cycle stability and price, so its application in chemical chain hydrogen production technology (CLH) is also the focus of the present invention.

[0053] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0054] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0055] Example 1

[0056] A spinel oxygen carrier with deep lattice oxygen release capability in this embodiment is prepared by the following method:

[0057] Weigh 0.25 mol of copper oxide (CuO) and 0.25 mol of ferric oxide (Fe2O3) powder and put them into a ball mill, add an appropriate amount of anhydrous ethanol, label it, put it symmetrically into the ball mill and tighten the clamping device; rotate it at 600 rpm, forward for 30 minutes, stop for 5 minutes, reverse for 30 minutes, and repeat 5 times, i.e., rotate for a total of 5 hours; put the mixture in the ball mill into a drying oven and dry it at 120°C for 8 hours, place the dried sample in a muffle furnace, calcine it at 900°C for 10 hours, and grind it to obtain an iron-based spinel sample recorded as CuFe2O4.

[0058] Example 2

[0059] A spinel oxygen carrier with deep lattice oxygen release capability in this embodiment is prepared by the following method:

[0060] Weigh 0.25 mol of calcium oxide (CaO) and 0.25 mol of ferric oxide (Fe2O3) powder and put them into a ball mill, add an appropriate amount of anhydrous ethanol, label them, put them symmetrically into the ball mill and tighten the clamping device; rotate at 600 rpm, forward for 30 min, stop for 5 min, reverse for 30 min, and repeat 5 times, i.e., rotate for a total of 5 h; put the mixture in the ball mill into a drying oven and dry it at 120°C for 8 h, place the dried sample in a muffle furnace, calcine it at 900°C for 10 h, and grind to obtain an iron-based spinel sample recorded as CaFe2O4.

[0061] Example 3

[0062] A spinel oxygen carrier with deep lattice oxygen release capability in this embodiment is prepared by the following method:

[0063] Weigh 0.25 mol of nickel oxide (NiO) and 0.25 mol of ferric oxide (Fe2O3) powder and put them into a ball mill, add an appropriate amount of anhydrous ethanol, label them, put them symmetrically into the ball mill and tighten the clamping device; rotate at 600 rpm, forward for 30 min, stop for 5 min, reverse for 30 min, and repeat 5 times, i.e., rotate for a total of 5 h; put the mixture in the ball mill into a drying oven at 120°C and dry it for 8 h, place the dried sample in a muffle furnace, calcine it at 900°C for 10 h, and grind to obtain an iron-based spinel sample recorded as NiFe2O4.

[0064] Example 4

[0065] A spinel oxygen carrier with deep lattice oxygen release capability in this embodiment is prepared by the following method:

[0066] Weigh 0.25 mol of manganese oxide (MnO) and 0.25 mol of ferric oxide (Fe2O3) powder and put them into a ball mill, add an appropriate amount of anhydrous ethanol, label it, put it symmetrically into the ball mill and tighten the clamping device; rotate it at 600 rpm, forward for 30 minutes, stop for 5 minutes, reverse for 30 minutes, and repeat 5 times, i.e., rotate for a total of 5 hours; put the mixture in the ball mill into a drying oven and dry it at 120°C for 8 hours, place the dried sample in a muffle furnace, calcine it at 900°C for 10 hours, and grind it to obtain an iron-based spinel sample recorded as MnFe2O4.

[0067] Example 5

[0068] A spinel oxygen carrier with deep lattice oxygen release capability in this embodiment is prepared by the following method:

[0069] Weigh 0.25 mol of strontium oxide (SrO) and 0.25 mol of ferric oxide (Fe2O3) powder and put them into a ball mill, add an appropriate amount of anhydrous ethanol, label them, put them symmetrically into the ball mill and tighten the clamping device; rotate at 600 rpm, forward for 30 min, stop for 5 min, reverse for 30 min, and repeat 5 times, i.e., rotate for a total of 5 h; put the mixture in the ball mill into a drying oven at 120°C and dry it for 8 h, place the dried sample in a muffle furnace, calcine it at 900°C for 10 h, and grind to obtain an iron-based spinel sample recorded as SrFe2O4.

[0070] Example 6

[0071] A spinel oxygen carrier with deep lattice oxygen release capability in this embodiment is prepared by the following method:

[0072] Weigh 0.05 mol of copper oxide (CuO), 0.05 mol of calcium oxide (CaO), 0.05 mol of nickel oxide (NiO), 0.05 mol of strontium oxide (SrO), 0.05 mol of manganese oxide (MnO) and 0.25 mol of ferric oxide (Fe2O3) powder and put them into a ball mill, add an appropriate amount of anhydrous ethanol, label them and put them symmetrically into the ball mill and tighten the clamping device; rotate forward for 30 minutes, stop for 5 minutes, reverse for 30 minutes, and repeat 5 times at a speed of 600 rpm, that is, rotate for a total of 5 hours; put the mixture in the ball mill into a drying oven at 120°C and dry for 8 hours, place the dried sample in a muffle furnace, calcine at 900°C for 10 hours, and grind to obtain an iron-based spinel sample recorded as Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 Fe2O4.

[0073] Comparative Example 1

[0074] Weigh 0.5 mol of ferric oxide (Fe2O3) powder and put it into a ball mill, add an appropriate amount of anhydrous ethanol, label it, put it symmetrically into the ball mill and tighten the clamping device; rotate it at 600 rpm, forward for 30 minutes, stop for 5 minutes, reverse for 30 minutes, and repeat 5 times, i.e., rotate for a total of 5 hours; put the mixture in the ball mill into a drying oven and dry it at 120°C for 8 hours, place the dried sample in a muffle furnace, calcine it at 900°C for 10 hours, and obtain the iron-based spinel sample Fe2O3 after grinding.

[0075] The test results are analyzed as follows:

[0076] XRD test The oxygen carriers prepared in Examples 1-6 and Comparative Example 1 were subjected to XRD test. The test results are as follows: Figure 3 and Figure 4 shown.

[0077] (1) By Figure 3 and Figure 4 It can be seen that all spinel samples crystallize in a cubic structure of the Fd-3m space group, and the diffraction peaks of each group of samples are consistent with the corresponding standard diffraction peaks (PDF) derived from the inorganic crystal structure database ICSD and there are no other impurity crystals, indicating that the binary spinel oxygen carrier prepared by ball milling has good crystallinity and the purity of the binary spinel oxygen carrier samples synthesized under all working conditions is very high.

[0078] (2) By Figure 4 It can be seen that fresh Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 Fe2O4 oxygen carriers mainly include four crystal phases: NiFe2O4 (PDF#10-0325), Ca 0.48 Sr 0.52 CuO2 (PDF#89-1665), NiMn2O4 (PDF#88-0241) and CuFe2O4 (PDF#34-0425). Comparing the XRD characteristic peaks of multi-element iron-based spinel oxygen carriers, it can be seen that the characteristic peaks of most spinel oxygen carriers are mainly concentrated near 2θ=30° and 2θ=60°, and with the increase of the number of added elements, the characteristic peaks of the samples tend to move to lower angles, which indicates that the lattice parameters have changed.

[0079] XPS test The oxygen carriers prepared in Examples 1-6 and Comparative Example 1 were subjected to XPS test. The test results are shown in Figure 5 shown.

[0080] (1) Under normal circumstances, adsorbed oxygen (O ads ) by OH - , O - , O 2- The composition tends to completely oxidize the fuel to produce CO2 and H2O. lat ) is usually less active and tends to partially oxidize the fuel into CO and H2, which is beneficial to the timely conversion of the fuel and the consumption of deposited carbon.

[0081] (2) Pure Fe2O3, CuFe2O4, NiFe2O4, MnFe2O4, SrFe2O4, CaFe2O4 and Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2The characteristic peak areas of adsorbed oxygen of Fe2O4 account for 38.4%, 41.4%, 30.2%, 27.4%, 18.3%, 39.6% and 38.2% of the total characteristic peak areas, respectively; the characteristic peak areas of lattice oxygen account for 61.6%, 58.6%, 48.4%, 65.8%, 12.6%, 50.8% and 52.0% of the total characteristic peak areas, respectively. 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 Fe2O4 lattice oxygen accounts for 52.0% and is relatively rich. According to the proportion of lattice oxygen content of different oxygen carriers, it can be inferred that pure Fe2O3, MnFe2O4 and Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 Fe2O4 has excellent hydrogen production capacity.

[0082] SEM test The fresh oxygen carrier prepared in Example 6 was subjected to SEM test. The test results are shown in Figure 2 shown.

[0083] Figure 2 For the treated Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 The SEM image of Fe2O4 shows that the sample has a typical irregular morphology with an average particle size of 70-100nm. The oxygen carrier is evenly distributed in particles with a relatively smooth surface without any visible secondary phase agglomeration, indicating that a multi-component spinel alloy has been generated, which is consistent with the XRD conclusion (2).

[0084] H2-TPR Test The oxygen carriers prepared in Examples 1-6 and Comparative Example 1 were subjected to XRD test. The test results are as follows: Figure 6 shown.

[0085] (1) H2-TPR studies the differences in lattice oxygen activity between different oxygen carriers. The peak area is proportional to the amount of H2 consumed, and the peak position corresponds to the reduction performance of the active substance. The lower the initial reduction temperature of the experiment, the stronger the adsorbed oxygen reaction activity is. The reducing gas is more easily completely oxidized to CO2 and H2O, while the reactions in the medium and high temperature zones can be considered to be the result of lattice oxygen consumption.

[0086] (2) Figure 6As shown in the figure, pure Fe2O3 begins to reduce at 476℃, with a peak area of ​​34.5 and low H2 consumption, indicating that the lattice oxygen activity is not high. When the temperature reaches 922.7℃, the peak area reaches a maximum of 287.9 ​​and the peak position also reaches the highest, indicating that the lattice oxygen activity is the highest and the reduction performance is the strongest at this temperature.

[0087] (3) Figure 6 As shown in the figure, when CuFe2O4 is at 276℃, the sample has already started to reduce, with a peak area of ​​281.3, a high H2 consumption, and the highest reduction performance of the oxygen carrier. The lattice oxygen activity is too high at this time, which is related to the enhanced oxygen release reaction activity of copper. When the temperature reaches 788.4℃, the peak area reaches a peak value of 501.2 again, which is much higher than that of pure Fe2O3, indicating that the H2 consumption is the highest at this temperature.

[0088] (4) Figure 6 As shown, the peak area of ​​NiFe2O4 is 105.8 at 624.7℃, which is the temperature at which NiFe2O4 has the strongest reduction performance. However, when the fixed bed is heated to 900℃, the reduction performance is already very low.

[0089] (5) Figure 6 As shown in the figure, when CaFe2O4 is at 490℃, the sample begins to reduce, with a peak area of ​​3.67 and a very low H2 consumption, indicating that the lattice oxygen activity is very low and basically no redox reaction occurs. When the temperature reaches 627℃ and 797.3℃, the peak areas reach 16.6 and 45.6 respectively, and the peak value is not reached until the temperature reaches 999.7℃. It is speculated that the temperature point at which CaFe2O4 reaches the highest reduction performance may exceed 1000℃.

[0090] (6) Figure 6 As shown, the peak areas of MnFe2O4 and SrFe2O4 reach the maximum when the temperature reaches 807.2℃ and 707.5℃, and the amount of hydrogen consumed is the largest, but the temperature corresponding to the point with the highest lattice oxygen activity in the oxygen carrier MnFe2O4 is 639.1℃, while the temperature corresponding to the highest lattice oxygen activity of the oxygen carrier SrFe2O4 is 707.5℃.

[0091] (7) Figure 6 It can be seen that at 383.5℃, the five-membered iron-based oxygen carrier Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2The Fe2O4 sample begins to reduce, which is lower than the pure Fe2O3 sample (around 476°C). At this time, the lattice oxygen reactivity is too high, which is related to the enhancement of oxygen release reaction activity by doping with copper. As the proportion of doped elements increases, the curve moves toward the low temperature direction, but decays rapidly after reaching the peak, which means that the mobility and reactivity of oxygen are improved. The abundant H2 consumption and the decline in the peak in the 600-750°C range indicate that the five-element iron-based oxygen carrier sample can oxidize part of the fuel to produce synthesis gas. In addition, the increase in hydrogen consumption in the low temperature zone indicates that 900°C as the reduction temperature of the fixed bed is sufficient for the oxygen carrier to release lattice oxygen, which provides a basis for the high conversion rate shown by the five-element iron-based oxygen carrier sample in the fixed bed experiment.

[0092] Application Examples

[0093] The schematic diagram of the spinel oxygen carrier with deep lattice oxygen release capability of the present invention in the chemical chain hydrogen production of waste plastics is as follows: Figure 1 .

[0094] The first application example: After the oxygen carrier is placed in a fixed bed reactor for pretreatment, the feed device is started to start the reaction. After the reaction is completed, water is introduced to prepare hydrogen. The details are as follows

[0095] Application Example 1

[0096] (1) The feed rate was set to 0.1 g / min, and 0.1 g of polypropylene (PP) powder was weighed and placed in the feeder. A certain mass of oxygen carrier Cu prepared in Example 6 with oxygen supply coefficients Φ of 0.5 and 1 was weighed. 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 Fe2O4 was placed on the porous distribution plate of the quartz tube reactor (the specific oxygen carrier mass weighed is shown in Table 3.2), the pipeline was connected, and the air tightness of the device was checked. The flow meter was controlled to pass nitrogen (99.9%, 200mL / min) for 20min to purge the entire reaction device to ensure that the tube was in an inert atmosphere.

[0097] (2) Turn on the power of the fixed bed reactor to heat the vertical tube furnace, the heating rate is 10°C / min, the carrier gas atmosphere is nitrogen (158mL / min) and oxygen (42mL / min), after the temperature of the vertical tube furnace reaches 900°C and remains stable, turn off the oxygen intake, set the carrier gas atmosphere nitrogen (99.9%, 200mL / min), and purge the reaction device for 10min to remove residual oxygen. Turn on the power of the vibrating feeder to start feeding. To ensure smooth feeding, the top of the feeder is connected to inert nitrogen. The polypropylene (PP) powder is brought into the fixed bed reactor by the nitrogen flow through the feed pipe to react with the oxygen carrier, and wait until the flue gas analyzer no longer detects the generation of gas.

[0098] (3) After all gas contents except nitrogen have dropped to zero, water is loaded into the fixed bed reactor at 0.1 mL / min using a metering pump to react with the oxygen carrier to produce hydrogen. When the flue gas analyzer no longer detects gas production, the reaction is considered to be over, and the metering pump is turned off to end the experiment. The hydrogen purity is the hydrogen concentration in the produced gas.

[0099] Application Example 2

[0100] The difference between this application example and application example 1 is that the oxygen carrier is different. The oxygen carrier is CaFe2O4 prepared in example 2.

[0101] Application Example 3

[0102] The difference between this application example and application example 1 is that the oxygen carrier is different. The oxygen carrier is NiFe2O4 prepared in example 3.

[0103] Application Example 4

[0104] The difference between this application example and application example 1 is that the oxygen carrier is different. The oxygen carrier is MnFe2O4 prepared in example 4.

[0105] Application Example 5

[0106] The difference between this application example and application example 1 is that the oxygen carrier is different. The oxygen carrier is SrFe2O4 prepared in example 5.

[0107] Application Example 6

[0108] The difference between this application example and application example 1 is that the oxygen carrier is different. The oxygen carrier is CuFe2O4 prepared in example 1.

[0109] Application Example 7

[0110] The difference between this application example and application example 1 is that the oxygen carrier is different. The oxygen carrier is Fe2O3 prepared in comparison example 1.

[0111] After the test reaction was completed, the hydrogen yield, purity and carbon conversion rate were summarized as shown in Table 1.

[0112] Table 1

[0113]

[0114] Discussion and Conclusion

[0115] (1) After the spinel oxygen carriers were prepared by ball milling and characterized, all the spinel oxygen carriers showed high crystallinity and purity, and the oxygen carriers were distributed in a granular form with a smooth surface. The spinel oxygen carriers have a high lattice oxygen content, among which pure Fe2O3, MnFe2O4 and Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 The lattice oxygen of Fe2O4 accounts for 61.6%, 65.8% and 52.0% respectively, indicating that oxygen carriers are more inclined to undergo partial redox reactions with fuels to generate CO and H2 during chemical chain hydrogen production. CuFe2O4 has a higher oxygen adsorption activity at 276°C in the low temperature range. In addition to CuFe2O4, other iron-based spinel oxygen carriers generally have stronger oxygen release capacity in the medium and high temperature range of 600-800°C, which also shows that the lattice oxygen activity of iron-based oxygen carriers is higher.

[0116] (2) Under the same oxygen supply coefficient, pure Fe2O3 and Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 Fe2O4 always shows better hydrogen production performance. When Φ=0.5, pure Fe2O3 and Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 The hydrogen yields of Fe2O4 can reach 8.24mmol / g and 6.76mmol / g, respectively, which are 2-3 times higher than those of other binary spinel oxygen carriers. The carbon conversion rate can reach 93.98% and 85.68%, which are also much higher than those of other binary iron-based oxygen carriers. This may be because the doped multi-metal elements have a dilution effect on the A-site atoms of the spinel oxygen carrier (AFe2O4), combined with the multi-metal effect that promotes the release of lattice oxygen, resulting in an increase in carbon conversion rate and H2 yield.

[0117] (3) Under different oxygen supply coefficients, the hydrogen production performance of the same oxygen carrier under Φ = 0.5 is better than that under Φ = 1. The hydrogen yield of pure Fe2O3 is increased from 2.69 mmol / g to 8.24 mmol / g, the carbon conversion rate is increased from 51.3% to 93.98%, and the Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 The hydrogen yield of Fe2O4 increased from 3.76mmol / g to 6.76mmol / g, and the carbon conversion rate increased from 77.06% to 85.65%. This is because within a certain range, a higher Φ value may cause the chemical chain hydrogen production process to transform into a chemical chain combustion process, resulting in a lower H2 yield and a higher CO2 content in the product, while a lower Φ value will promote the deep release of oxygen carriers, and releasing more lattice oxygen will be more conducive to the synthesis of H2.

[0118] (4) Through XRD and SEM characterization analysis of the oxygen carriers after the reaction, it was found that pure Fe2O3 was basically converted into Fe3O4 after the reaction and was difficult to regenerate, while the cyclic performance of binary iron-based spinel oxygen carriers doped with other metals and pentavalent iron-based spinel oxygen carriers were significantly better than that of pure Fe2O3.

[0119] Based on the above analysis, the five-element iron-based spinel oxygen carrier Cu 0.2 Ca 0.2 Ni 0.2 Mn 0.2 Sr 0.2 Fe2O4 shows excellent results in both hydrogen production performance and cycle performance. Therefore, the five-element iron-based spinel oxygen carrier will have a good development prospect in the field of chemical loop hydrogen (CLH) and is expected to stand out from the chemical loop technology.

Claims

1. A method for preparing a spinel oxygen carrier with deep lattice oxygen release capability, characterized in that: The method steps are as follows: The metal oxide, ferric oxide powder and organic solvent are mixed in order according to the proportion, and the obtained mixture is ground and then dried; then the dried precursor is calcined at a temperature of 900° C. for 10 hours, and the obtained product is ground to obtain the spinel oxygen carrier with deep lattice oxygen release ability.

2. The preparation method according to claim 1, characterized in that: The metal oxide is at least one of CuO, MnO, NiO, CaO and SrO.

3. The preparation method according to claim 2, characterized in that: The metal oxide consists of copper oxide CuO, manganese oxide MnO, nickel oxide NiO, calcium oxide CaO and strontium oxide SrO.

4. The preparation method according to claim 3, characterized in that: The metal oxide (M i )Amount of substance Mol Mi The amount of ferric oxide Mol Fe Satisfies the following relationship: (∑Mol Mi :Mol Fe )=1:

1.

5. The spinel oxygen carrier with deep lattice oxygen release capability prepared by the preparation method according to any one of claims 1 to 4.

6. Application of the spinel oxygen carrier with deep lattice oxygen release capability prepared by the preparation method according to any one of claims 1 to 4 in the production of high-purity hydrogen using waste plastics as raw materials based on chemical chain hydrogen production technology.

7. The use according to claim 6, characterized in that: The specific method of the application comprises the following steps: (1) Pre-set the feed rate, then weigh the polypropylene PP powder and place it in the feeder; place the spinel oxygen carrier with deep lattice oxygen release capacity on the porous distribution plate of the quartz tube reactor according to the ratio, connect the pipeline, and check the air tightness of the device; control the flow meter to pass nitrogen to purge the entire reaction device to ensure that the tube is in an inert atmosphere; (2) turning on the power of the fixed bed reactor to heat the vertical tube furnace and introducing a carrier gas atmosphere; after the temperature of the vertical tube furnace reaches 900° C. and remains stable, closing the oxygen intake, maintaining the flow rate of the carrier gas atmosphere unchanged, and purging the reaction device to remove residual oxygen; then turning on the power of the vibrating feeder to start feeding, and the polypropylene powder is brought into the fixed bed reactor through the feed pipe to react with the deep lattice oxygen release capacity spinel oxygen carrier until the flue gas analyzer can no longer detect the generation of gas; (3) When the contents of all gases except nitrogen are reduced to 0, deionized water is loaded into the fixed bed reactor by a metering pump to react with the reduced oxygen carrier to produce hydrogen; when the flue gas analyzer no longer detects gas generation, the reaction is completed, the metering pump is turned off, and the experiment is ended; the hydrogen purity is the hydrogen concentration in the produced gas.

8. The use according to claim 7, characterized in that: The mass of the spinel oxygen carrier with deep lattice oxygen release capacity in step (1) is the mass of the oxygen carrier when the oxygen supply coefficient is Φ=1 and Φ=0.5 respectively.

9. The use according to claim 7, characterized in that: The heating rate in step (2) is 5-15°C / min.

10. The use according to claim 7, characterized in that: The step (2) is carried out in a fuel reactor (FR), the step (3) is carried out in a steam reactor (SR), and the fixed bed reactor is composed of a vertical tube furnace and a quartz tube reactor.

Citation Information

Cited By

  • Method for preparing synthesis gas from plastic and high-entropy oxide

    CN122168337A